Green Investing and Political Behavior - Heeb, Florian; Kölbel, Julian F; Ramelli, Stefano; Vasileva, Anna (Review of Financial Studies, 2026)
Abstract A fundamental concern about green investing is that it may crowd out political support for public policies addressing negative externalities. We examine this concern in a preregistered experiment conducted shortly before a real referendum on a climate law in Switzerland. We find that offering an opportunity to invest in a climate-friendly fund does not reduce individual support for climate regulation, measured by political donations and voting intentions. A replication of the experiment in the United Kingdom yields similar results. Our estimates reject a crowding-out effect, suggesting instead a modest crowding-in effect of green investing on political support for green policies.